Analysis of D-Q small-signal impedance of back-to-back frequency converter - Cai, Zhongqi; Han, Jizhi; Chen, Jianfu; Gan, Deshu; Zhang, Haitao; Wang, Xiuli (Frontiers in Energy Research, 2023)
The back-to-back frequency converter plays a vital role in the formation of the fractional frequency transmission system Despite their numerous advantages, however, impacted by the unique impedance characteristics of power electronics, the wide-band oscillations occur more frequency as well as more common recently, which have posed great challenges to the system operation and raised great concern over the researchers worldwide. To address this issue and properly investigate the impedance characteristics of the back-to-back frequency converter, this manuscript establishes the small-signal impedance of the back-to-back frequency converter with inner current control loop and outer voltage/power control loop in the synchronous reference (dq) frame. Then, by using the impedance model and determinant-based General Nyquist Criterion (GNC), the stability assessment and instability cause identification are studied. Finally, the analysis presented in this paper is verified based on frequency and time-domain simulations in the MATLAB/Simulink environment.